2022
DOI: 10.1530/eje-22-0187
|View full text |Cite
|
Sign up to set email alerts
|

Management of cranial diabetes insipidus: clinical outcomes and patient perception of care

Abstract: Objective: There is growing recognition of morbidity and mortality that can occur in patients with cranial diabetes insipidus (CDI) during hospitalisation, due to prescribing errors and dysnatraemia, often related to confusion between CDI and diabetes mellitus amongst non-specialists. Methods: Data for each hospitalisation in patients with CDI attending OUH were collected retrospectively. The same cohort were invited to complete a questionnaire by telephone. Results: 109 patients were included, median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…4 In line with this and a study by Dilrukshi and colleagues, 24% of the hospitalised patients in our survey reported problems accessing desmopressin during routine or emergency hospitalisations, most commonly due to non-availability. 29 Owing to its rarity, central diabetes insipidus is a neglected condition among health-care professionals, and increased awareness of this disease is urgently needed. Additionally, central diabetes insipidus is often confused with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…4 In line with this and a study by Dilrukshi and colleagues, 24% of the hospitalised patients in our survey reported problems accessing desmopressin during routine or emergency hospitalisations, most commonly due to non-availability. 29 Owing to its rarity, central diabetes insipidus is a neglected condition among health-care professionals, and increased awareness of this disease is urgently needed. Additionally, central diabetes insipidus is often confused with diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%